1992
DOI: 10.1128/aac.36.11.2398
|View full text |Cite
|
Sign up to set email alerts
|

Stability of antimycobacterial drugs in susceptibility testing

Abstract: Aqueous solutions of0.02% isoniazid, 0.2% streptomycin, 0.2%para-aminosalicylate, and 0.5% ethambutol and ethylene glycol solutions of 0.5% ethionamide stored at 3 to 7°C remained stable for 1 year, as did aqueous solutions of 0.05% ethionamide hydrochloride, 0.05% kanamycin, 0.05% viomycin, and 0.1% capreomycin stored at -20°C. The (Wheaton Co., Millville, N.J.).Stability at 3 to 7°C was investigated in distilled water solutions of 0.5% ethambutol (EMB), 0.02% isoniazid (INH; isonicotinylhydrazine), 0.2% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 5 publications
3
14
0
1
Order By: Relevance
“…For the RIF stock solution, our data indicate that RIF stock solution kept either at 4°C or at Ϫ20°C is eligible for reuse at least within 3 months. Those outcomes are consistent with those reported previously by Griffith and Bodily (5). Even though the RIF stock solution is relatively stable, long-term storage is not recommended, since an evaporation of organic solvent will occur even for solutions kept at Ϫ20°C.…”
Section: Discussionsupporting
confidence: 81%
“…For the RIF stock solution, our data indicate that RIF stock solution kept either at 4°C or at Ϫ20°C is eligible for reuse at least within 3 months. Those outcomes are consistent with those reported previously by Griffith and Bodily (5). Even though the RIF stock solution is relatively stable, long-term storage is not recommended, since an evaporation of organic solvent will occur even for solutions kept at Ϫ20°C.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, due to the small difference between the critical concentration used for EMB drug susceptibility testing and the MIC, conventional drug susceptibility testing for EMB is less reliable, yields less reproducible results, and has a lower sensitivity when compared with other drugs. 1 Another reason for the difficulties in conventional EMB resistance testing might probably a lower stability of this drug during incubation at 37 C. 22 This might be further complicated by the presence of heteroresistant populations that, based on the amount of susceptible and resistant cells, might lead to false susceptible test results. In addition, sub culturing of heteroresistant strains is likely to cause non reproducible test results e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity (61.2%) and specificity (84.8%) of detection of EMB resistance were indeed lower than were seen with the other drugs; however, this does not necessarily mean that the assay has a low predictive value for clinically relevant EMB resistance. Conventional phenotypic EMB DST for M. tuberculosis is notoriously problematic (12,27). Several studies, including allelic exchange experiments, have demonstrated a strong association between embB mutations, specifically at codon 306, and EMB resistance (35-37, 44, 51, 52).…”
Section: Discussionmentioning
confidence: 99%